Additive manufacturing of Al2O3 ceramics with MgO/SiC contents by laser powder bed fusion process - Ur Rehman, Asif; Ullah, Abid; Liu, Tingting; Ur Rehman, Rashid; Salamci, Metin U. (Frontiers in Chemistry, 2023)
Laser powder bed fusion is a laser-based additive manufacturing technique that uses a high-energy laser beam to interact directly with powder feedstock. LPBF of oxide ceramics is highly desirable for aerospace, biomedical and high-tech industries. However, the LPBF of ceramics remains a challenging area to address. In this work, a new slurry-based approach for LPBF of ceramic was studied, which has some significant advantages compared to indirect selective laser sintering of ceramic powders. LPBF of Al2O3 was fabricated at different MgO loads up to 80 wt%. Several specimens on different laser powers (70 W–120 W) were printed. The addition of magnesia influenced the microstructure of the alumina ceramic significantly. The findings show that when the laser power is high and the magnesia load is low, the surface quality of the printing parts improves. It is feasible to produce slurry ceramic parts without binders through LPBF. Furthermore, the effects of SiC and MgO loads on the microstructure and surface morphology of alumina are compared and analysed.